PENGEMBANGAN USAHA ROTI KETAWA DENGAN RANCANG BANGUN MESIN PENGADUK ADONAN ROTI DAN MESIN SPINNER UNTUK MENINGKATKAN PRODUKSI ROTI KETAWA (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Appropriate technology in the process of making bread dough is needed to make the manufacturing process more faster which in turn will increase productivity. The process of mixing the tawa bread dough at the Roti Ketawa Business in Melati II Duku Village, Perbaungan District, Serdang Bedagai Regency, the average production capacity per day uses 300 kg of wheat flour, and is still done manually using human hands. The quality of the dough results still leaves yields and dough that is not homogeneous and takes one working day from a worker with a wage of Rp. 150,000. Work equipment still pays less attention to hygienic factors. The process of draining oil from the results of frying the dough is still manual, namely by drying on paper and has not provided production process in effectively and efficiently. The use of bread dough mixing machines, spinning machines, electric thermal sealers, cooking stoves and work tables for the process of cutting dough with ceramic materials is an appropriate technology that can be applied to make the production process more effectively and efficiently so that lower yields are obtained. economic value in the production process. laughter bread, when compared to the previous production process (manual). The cost of mixing into dough Rp. 50,000 per day, takes up to 4 hours and makes the packaging process more practical and product packaging more attractive.